Education Sector Analysis - Ministry of Education, Science, and Technology (2019)

Education Sector Analysis - Ministry of Education, Science, and Technology (2019)

Alternative Education Systems Implementation Guide - Ministry of Education, Science and Technology (Republic of South Sudan, 2013)

Education Sector Development Plan (2016/17 – 2020/21). Mainland Tanzania. - Ministry of Education, Science and Technology (2018)

Proposal to the Global Partnership for Education for a contribution towards the implementation of the 2018-2020 Education Sector Plan - Ministry of Education, Science and Technology (Government of Sierra Leone; UNICEF, 2018)

Education Sector Plan, 2018-2020: Getting It Right – Service Delivery, Integrity and Learning in Sierra Leone - Ministry of Education, Science and Technology (Government of Sierra Leone, 2018)

Sierra Leone: Education Country Status Report: An analysis for further improving the quality, equity and efficiency of the education system in Sierra Leone - Ministry of Education, Science and Technology (Government of Sierra Leone, 2013)

Education sector development plan 2016/17 – 2020/21: Tanzania mainland - Ministry of Education, Science and Technology (The United Republic of Tanzania, 2018)

Education sector performance report 2017/2018: Tanzania mainland - Ministry of Education, Science and Technology (United Republic of Tanzania, 2018)

GPE Covid-19 Education Response Support Programme (CESP) - Ministry of Education, Science and Technology (The United Republic of Tanzania, 2020)

National Framework for Continuous Professional Development for Practicing Teachers - Ministry of Education, Science and Technology (United Republic of Tanzania, 2017)
Keywords: _B:important; _G:important; _G:reviewed; _Tanzania; _final_bib; _important

National Framework for Teachers Continuous Professional Development - Ministry of Education, Science and Technology (United Republic of Tanzania, 2020)

Education sector development plan 2016/17–2020/21: Tanzania mainland - Ministry of Education, Science and Technology (The United Republic of Tanzania, 2018)

Kenya Education Sector Support Programme 2005 - 2010 - Ministry of Education, Science and Technology (2005)

Education Sector Analysis - Ministry of Education, Science, and Technology (Government of the Republic of Malawi, 2019)

School Level MEWAKA Implementation Guidelines - Ministry of Education, Science and Technology (2022)

TCPD Supervision Guidelines - Ministry of Education, Science and Technology (2022)
MWONGOZO WA KUSIMAMIA UTEKELEZAJI WA MPANGO WA MAFUNZO ENDELEVU KWA WALIMU KAZINI

Education Sector Analysis - Ministry of Education, Science, and Technology (Government of the Republic of Malawi, 2019)

National Education Policy - Ministry of Education, Science and Technology (Government of the Republic of Malawi, 2016)

Ministry of Education, Science and Technology – Policy Reforms - Malawi Ministry of Education, Science and Technology (2019)
The Malawi Public Sector Reforms Management Unit exists to catalyse, drive and facilitate public sector reforms in Malawi. The reforms are implemented in Government ministries, departments and agencies (MDAs), local councils, parastatal organizations and constitutional bodies.

Kaduna State Education Sector Strategic Plan 2019–2029 - Kaduna State Ministry of Education, Science, and Technology (2019)

Education Sector Plan 2018-2020 - Ministry of Education, Science and Technology (Sierra Leone) (2018)

Proposal to the Global Partnership for Education for a contribution towards the implementation of the 2018-2020 Education Sector Plan - Ministry of Education, Science and Technology (Sierra Leone) (2018)

Malawi Education Sector Analysis - Malawi Ministry of Education, Science, and Technology, Malawi (Government of Malawi, 2019)

Global Initiative on Out-of-School Children: Tanzania Country Report - UNICEF; Ministry of Education, Science and Technology; UNESCO (UNICEF, United Republic of Tanzania, UNESCO, 2018)